Learning styles, academic achievement, and mental health problems among medical students in Thailand - Salilthip Paiboonsithiwong (2018)
PURPOSE: This study aimed to investigate the prevalence of various learning styles among medical students and their correlations with academic achievement and mental health problems in these students.METHODS: This study was conducted among 140 first-year medical students of Chiang Mai University, Thailand in 2014. The participants completed the visual-aural-read/write-kinesthetic (VARK) questionnaire, the results of which can be categorized into 4 modes, corresponding to how many of the 4 types are preferred by a respondent. The 10-item Perceived Stress Scale (PSS-10) and the 21-item Outcome Inventory (OI-21) were also used. The participants' demographic data, grade point average (GPA), and scores of all measurements are presented using simple statistics. Correlation and regression analysis were employed to analyze differences in the scores and to determine the associations among them.RESULTS: Sixty percent of the participants were female. The mean age was 18.86±0.74 years old. Quadmodal was found to be the most preferred VARK mode (43.6%). Unimodal, bimodal, and trimodal modes were preferred by 35%, 12.9%, and 18.6% of the participants, respectively. Among the strong unimodal learners, visual, aural, read/write, and kinesthetic preferences were reported by 4.3%, 7.1%, 11.4%, and 12.1% of participants, respectively. No difference was observed in the PSS-10, OI-anxiety, OI-depression, and OI-somatization scores according to the VARK modes, although a significant effect was found for OI-interpersonal (F=2.788, P=0.043). Moreover, neither VARK modes nor VARK types were correlated with GPA.CONCLUSION: The most preferred VARK learning style among medical students was quadmodal. Learning styles were not associated with GPA or mental health problems, except for interpersonal problems.